Production of Low Fat Ice Cream from Black Glutinous Rice Milk - Charoenphun, Narin (Journal of Food Technology, Siam University, 2019)
Ice cream is a frozen dairy product. It is popular in the widespread consumption. However, there are some consumers lacking lactase enzyme in the intestine or they are allergic to milk protein. As a result, they are not able to consume dairy products. This research aims to develop healthy ice cream products that are suitable for consumers, who are allergic to cow milk. The optimum formula for producing ice cream from milk rice consisting of rice berry, black glutinous rice and rice berry mixed with black glutinous rice (50:50) as compared with milk ice cream (control) were studied. Physical properties and sensory evaluation by 9-point hedonic scales of ice cream were investigated. The result showed that the control formula had the highest percentage of overrun as followed by rice berry formula. Interestingly, black glutinous rice formula had higher overall liking score (7.73±0.88) than rice berry and mixed formula. Therefore, black glutinous rice formula was selected for studying in the replacement of dairy whipping cream by using cavendish banana, sunchoke, soy milk and glucose syrup. The result indicated that cavendish banana replacement in dairy whipping cream formula had the highest overall liking score (7.50±0.90). Apparently, the overrun, viscosity and melting rate were 26.40±0.15%, 655.00±3.33 cP and 0.08±0.01 g/min, respectively. Fat content of cavendish banana formula was 1.06%, which was lower than that of dairy whipping cream formula (5.87%). Therefore, rice milk ice cream reducing fat content are good as healthy food products and suitable for milk allergy consumers.